The Effect of Using Group Work Technique on Students’ Reading Comprehension - Annisa Tul Ulatifah; N. nuardi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This research was aimed to find out The Effect of Using Group Work Technique on Students’ Reading Comprehension. The design of this research was quasi experimental. The population was the total of tenth grade students that consist of 10 classess. Meanwhile the sample was proportion of the population that consist of 2 classes. X6 was experimental class and X9 was control class. The number of sample was selected by using cluster sampling. To analyze the data the writer gave pretest and posttest then analyzed the data by using independent sample t-test by using SPSS 16 version and effect size formula. After analyzing the data, the 2-tailed value was smaller than 0.05 (0.000 < 0.05). The result of effect size was 0.3 categorized as large effect. Thus, null hypothesis (Ho) is rejected, and alternative hypothesis (Ha) is accepted. So, it can be concluded that there was a significant effect of using Group Work Technique on Students’ Reading Comprehension